RNA sequencing of the lncRNA regulome modulated by Withania somnifera in human neuroblastoma SK-N-SH cells - Eshita Sharma; Dilip Mehta; Simran Sahare; Saiprasad Ajgaonkar; Praful Saha; Anand Bhaskar; Jash Trivedi; Dhananya S.; Manju Moorthy; Gopalakrishna Ramaswamy; Sujit Nair (Molecular Biology Reports, 2025)
Background The dysregulation of long-chain noncoding RNAs (lncRNAs) causes several complex human diseases including neurodegenerative disorders across the globe. Methods and results This study aimed to investigate lncRNA expression profiles of Withania somnifera (WS)-treated human neuroblastoma SK-N-SH cells at different timepoints (3 & 9 h) and concentrations (50 & 100 µg/mL) using RNA sequencing. Differential gene expression analysis showed a total of 4772 differentially expressed lncRNAs, out of which 3971 were upregulated and 801 were downregulated compared to controls. Differential gene expression was observed in dose-dependent (30 upregulated, 25 downregulated, 100 µg/mL 3 h vs. 50 µg/mL 3 h; 36 upregulated, 247 downregulated, 100 µg/mL 9 h vs. 50 µg/mL 9 h) and temporal kinetics (79 upregulated, 64 downregulated, 50 µg/mL 9 h vs. 50 µg/mL 3 h; 22 upregulated, 200 downregulated, 100 µg/mL 9 h vs. 100 µg/mL 3 h). Enrichment analysis showed that modulated lncRNAs were mainly implicated in GPCR ligand binding, HDACs and HATs histones, cellular senescence, cell cycle and post-translational protein modifications. Dysregulated lncRNAs upon WS treatment included BACE1-AS, MALAT1, SNHG1, HOTAIR, MEG3, BDNF-AS, and SHANK2-AS1 which are potential biomarkers in several neurodegenerative diseases. Co-expression analysis revealed that genes such as HMOX1, CHGB, SLC7A11, NOS1, KCNJ and NPY2R may be important in neurodegenerative disorders. Conclusions Taken together, our results indicated that WS treatment modulated several differentially expressed lncRNAs with putative regulatory potential in various neurodegenerative disorders. To the best of our knowledge, the lncRNA regulome that elicits the health-beneficial effects of WS has not been delineated thus far.